A data-driven CUF-based beam model based on the tree-search algorithm. (15th November 2022) - Hui, Yanchuan; Bai, Xiaowei; Yang, Yichen; Yang, Jie; Huang, Qun; Liu, Xiao; Huang, Wei; Giunta, Gaetano; Hu, Heng
Abstract: Data-driven Computational Mechanics (DDCM) has been proposed as a new computational paradigm in recent years. Most of the DDCM models are discretised in the FEM framework. In this paper, two strategies are employed in the framework of DDCM to improve computational efficiency. Firstly, an advanced structural theory, Carrera Unified Formula, is used to build the numerical model, which reduces the computational cost (amount of gauss points) and the number of iterations. Secondly, the tree-search algorithm is employed to build the hierarchical database, which speeds up the data searching efficiency. The corresponding results are compared with the FEM model, FE 2 model and FEM-based data-driven model to verify the proposed scheme. Some numerical cases have been conducted to demonstrate the validation and robustness of the hierarchical database.